2018
DOI: 10.1111/age.12654
|View full text |Cite
|
Sign up to set email alerts
|

Detection of genetic variants between different Polish Landrace and Puławska pigs by means of RNA‐seq analysis

Abstract: Variant calling analysis based on RNA sequencing data provides information about gene variants. RNA-seq is cheaper and faster than is DNA sequencing. However, it requires individual hard filters during data processing due to post-transcriptional modifications such as splicing and RNA editing. In the present study, RNA-seq transcriptome data on two Polish pig breeds (Puławska, PUL, n = 8, and Polish Landrace, PL, n = 8) were included. The pig breeds are significantly different with regard to meat qualities such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…Repeat sequences were inferred to comprised 33.1% of the genome in L. guanicoe, 32.7% in V. vicugna, and 27.02% in L. glama, lower values than in most mammals [11], although such sequences were difficult to assemble most likely due to the limitations of short-read sequencing. Resequencing of seven individuals per species (Additional file 1: Figure S2; Table S8) yielded an average sequence depth of 16-fold after filtering (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) Gb, Additional file 1: Table S9). Resequencing uncovered 21.3 million SNPs and a heterozygous SNP rate of 0.0030 for alpaca, 25.2 million and 0.0023 for vicuña, 16.7 million and 0.0018 for guanaco, and 16.1 million and 0.0020 for llama, indicating a higher overall SNP rate for the Vicugna lineage.…”
Section: De Novo Sequencing Assembly and Resequencingmentioning
confidence: 99%
“…Repeat sequences were inferred to comprised 33.1% of the genome in L. guanicoe, 32.7% in V. vicugna, and 27.02% in L. glama, lower values than in most mammals [11], although such sequences were difficult to assemble most likely due to the limitations of short-read sequencing. Resequencing of seven individuals per species (Additional file 1: Figure S2; Table S8) yielded an average sequence depth of 16-fold after filtering (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) Gb, Additional file 1: Table S9). Resequencing uncovered 21.3 million SNPs and a heterozygous SNP rate of 0.0030 for alpaca, 25.2 million and 0.0023 for vicuña, 16.7 million and 0.0018 for guanaco, and 16.1 million and 0.0020 for llama, indicating a higher overall SNP rate for the Vicugna lineage.…”
Section: De Novo Sequencing Assembly and Resequencingmentioning
confidence: 99%
“…These results support that higher expression of CTSC is associated with a higher activation of the proteolysis process favoring the meat tenderization. Besides, in a variant calling analyses based on RNA-seq data of two Polish pig breeds divergent for meat tenderness, variants with different genotype distribution between breeds on CTSC gene were detected [ 38 ]; however, any association analyses between the genetic variants identified and tenderness have been carried out so far.…”
Section: Discussionmentioning
confidence: 99%
“…In other study it was also shown that SNP in pituitaryspecific transcription factor 1 (PIT1) is associated with growth traits (feed:gain ratio, daily feed intake, number of days in experiment) and carcass traits (average backfat thickness, loin eye area, lean meat percentage) (Piórkowska et al, 2013). The newest report, based on RNA-Seq analysis, proved that polymorphism in aldehyde dehydrogenase 3 family member A2 (ALDH3A2) affects the weight of the ham and loin eye area, however in myomesin-1 (MYOM1) -meatiness and loin texture parameters in Polish Landrace and Puławska pigs (Piórkowska et al, 2018). Examples mentioned above prove the validity and reliability of studies that concern genetic markers in pigs.…”
Section: Introductionmentioning
confidence: 96%